KAI2-dependent signaling controls vegetative reproduction in Marchantia polymorpha through activation of LOG-mediated cytokinin synthesis (14) - Aino Komatsu; Mizuki Fujibayashi; Kazato Kumagai; Hidemasa Suzuki; Yuki Hata; Yumiko Takebayashi; Mikiko Kojima; Hitoshi Sakakibara; Junko Kyozuka (Nature Communications)
Abstract Marchantia polymorpha reproduces vegetatively (asexually) by producing propagules known as gemmae within gemma cups and sexually through spores. We previously reported that KARRIKIN INSENSITIVE2 (KAI2)-dependent signaling promotes gemma cup and gemma formation. KAI2A perceives unidentified endogenous ligand(s), tentatively referred to as KAI2 ligands (KL). Perception of KL by KAI2 triggers MORE AXILLARY GROWTH2 (MAX2)-dependent proteolysis of MpSUPPRESSOR of MORE AXILLALRY GROWTH2 1-LIKE (MpSMXL). In this study, we identify genes working downstream of KAI2-dependent signaling in M. polymorpha. We find that KAI2-dependent signaling positively controls the expression of MpLONELY GUY (MpLOG), encoding a cytokinin biosynthesis enzyme. Disruption of the MpLOG function decreases endogenous cytokinin levels and causes defects similar to KAI2-dependent signaling mutants. Moreover, supplying exogenous cytokinins rescues the defects of Mplog and KAI2-dependent signaling mutants, implying that cytokinins work downstream of KAI2-dependent signaling. Activation of MpLOG by KAI2-dependent signaling occurs in a highly cell-type-specific manner, leading to cell-specific induction of GEMMA CUP-ASSOCIATED MYB1 (GCAM1), the master regulator of vegetative reproduction of M. polymorpha. We propose a genetic cascade, starting from KAI2-dependent signaling, that promotes vegetative reproduction through the induction of MpLOG and GCAM1. The interaction between KAI2-dependent signaling and cytokinin in M. polymorpha provides insights into the function and evolution of KAI2-dependent signaling.